Photoluminescent and storage properties of photostimulable core/shell type silicate nanoparticles. Issue 2 (21st December 2012) - Osvet, Andres; Batentschuk, Miroslaw; Milde, Moritz; Lundt, Nils; Gellermann, Carsten; Dembski, Sofia; Winnacker, Albrecht; Brabec, Christoph J.; Stanek, Christopher R.; Nikl, Martin; Kovács, László; Greulich‐Weber, Siegmund
Abstract We have prepared hybrid luminescent nanoparticles with amorphous SiO2 cores and crystalline Zn2SiO4:Mn2+shells by sol‐gel technology. Under UV excitation the shells of the particles emit green Mn2+‐related luminescence at 525 nm. In addition, under the UV excitation at least two kinds of traps are filled with electrons, contributing to a long afterglow and photostimulated luminescence. The paper presents the details of the charging and stimulation characteristics of the photostimulated luminescence. (© 2012 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)